2002
DOI: 10.1046/j.1439-0442.2002.00426.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Malnutrition on the Expression of Daintain/AIF‐1 in the Gut Mucosa of Pigs

Abstract: The allograft inflammatory factor (AIF-1/daintain) is a hormone-like peptide produced by activated monocytic cells in a variety of traumatic, inflammatory and degenerative lesions. Gut-derived AIF-1 has been shown to modulate insulin production and to attenuate autoimmune diabetes. As the localization of this gastrointestinal peptide in the porcine duodenum is not known and the pig is a convenient model for the study of nutritional modulation of the mucosal immune compartment, we have localized expression of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…It was also shown in a human system that mRNA of AIF‐1 was expressed in the liver, colon and small intestine 10,14 . However, immunological functions of AIF‐1 in the gastrointestinal tract have been totally unclear, although Mentschel et al 15 . reported that AIF‐1 expression was elevated in the gut mucosa of malnourished pigs compared to optimally fed controls.…”
Section: Introductionmentioning
confidence: 99%
“…It was also shown in a human system that mRNA of AIF‐1 was expressed in the liver, colon and small intestine 10,14 . However, immunological functions of AIF‐1 in the gastrointestinal tract have been totally unclear, although Mentschel et al 15 . reported that AIF‐1 expression was elevated in the gut mucosa of malnourished pigs compared to optimally fed controls.…”
Section: Introductionmentioning
confidence: 99%
“…(3) Also, daintain is a novel marker for the study of nutritional regulation of the mucosal immune system of the pig. (4) Daintain shares a widespread identical amino acid sequence with allograft inflammatory factor-1 (AIF-1), (5) which is a 17-kDa interferon-␥-inducible Ca 2ϩ -binding protein and is encoded within the HLA class III genomic region. (6) AIF-1 was originally cloned from activated macrophages in a rat undergoing chronic transplant rejection.…”
Section: Introductionmentioning
confidence: 99%